Students discipline problems perception of counseling services: a qualitative analysis - Abu Yazid Abu Bakar; Cynthia Shamini Dawson; Ifdil Ifdil (RedWhite Press, 2020)
This study aims to discuss the perceptions of high school students towards guidance and counseling services. The aim of this study is to identify students’ perceptions of counseling sessions and to identify the services that students prefer. The sample of this study is 4 students comprising form four and five who attend national school from a famous Tuition Center in Butterworth, Penang. This study used interview sessions to collect data. The interview protocol comprises 10 unstructured questions that include the student’s background, situation at home, the reasons they do not see the counselor and the student’s choice of services other than counseling. We conducted theme analysis based on the respondents’ feedback. The results showed that students had a negative perception regarding meetings with counselors.